2021
DOI: 10.1055/a-1516-4139
|View full text |Cite
|
Sign up to set email alerts
|

Injury Profile among Elite Youth Male Football Players in a German Academy

Abstract: Studies that report injuries in elite youth football players are scarce. So far, no such studies have been reported in Germany. The aim of this study is to descriptively and statistically report the incidence of injuries that resulted in time-loss ≥ 4 days in the TSG Hoffenheim football academy by 138 male players aged between 12 and 19 years during one season. A total of 109 injuries were sustained by 76 players: 6.9 injuries occurred per 1000 hours of matches (95% CI, 5.0–9.6) and 0.7 injuries per 1000 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…The proportion of apophysitis incidence in overall incidence of 21% in our cohort exceeds the range of 3% to 17% found in existing literature. These are merely comparisons in proportion of incidence; due this relative incidence is comparable with existing literature [5,8,9,[11][12][13][14][15][16][17][18][19][20][21]. The injury type apophysitis has the greatest impact (5 days lost per player season) on players' availability due to a high severity.…”
Section: Injury Incidence By Location and Typesupporting
confidence: 68%
See 1 more Smart Citation
“…The proportion of apophysitis incidence in overall incidence of 21% in our cohort exceeds the range of 3% to 17% found in existing literature. These are merely comparisons in proportion of incidence; due this relative incidence is comparable with existing literature [5,8,9,[11][12][13][14][15][16][17][18][19][20][21]. The injury type apophysitis has the greatest impact (5 days lost per player season) on players' availability due to a high severity.…”
Section: Injury Incidence By Location and Typesupporting
confidence: 68%
“…Previous epidemiological studies in elite youth soccer reported an injury incidence ranging from 0.4 to 2.2 injuries per player season [5][6][7][8][9][10][11][12]. The most common injuries were muscle [5,8,9,[11][12][13][14][15][16][17][18][19][20][21] and/or ligament injuries [6,12,22]. Most studies report a linear distribution across age groups; the injury incidence increased with age.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Injury severity is commonly calculated as the number of days elapsed from the day of injury until the day the player returns to full training and/or is available for match selection ( 64 ), often presented as the proportion of injuries falling within defined bins (e.g., percentage of all injuries lasting 7–28 days). Although cut-offs vary slightly between studies and the choice of injury definition affects distributions, the combined findings suggest that 38% (7–74%) of injuries in boys last less than a week, another 38% (16–67%) last between a week and a month, while every fifth injury (21%, 2–37%) lasts more than a month ( 18 , 20 , 21 , 23 , 25 , 28 , 29 , 31 – 37 , 39 , 41 , 46 , 48 , 49 , 53 56 , 61 ). For girls, a larger proportion of “mild” injuries is observed, with around a half (51%, 38–52%) lasting a week or less, a third (36%, 32–41%) between a week and a month, and the remaining 16% (12–20%) more than a month ( 55 , 58 , 60 ).…”
Section: Injury Patterns In High-level Youth Footballmentioning
confidence: 99%
“…One approach to determining the extent of injuries is to count how many players sustain at least one injury over a season. In boys, this has ranged from 38 to 85% ( 18 25 ), with 0.4–2.2 injuries per player per season ( 19 42 ). Only one study reported seasonal injury proportion for girls (37%) ( 43 ), with another finding an average of 4.3 injuries per player per season ( 44 ).…”
Section: Injury Patterns In High-level Youth Footballmentioning
confidence: 99%
See 1 more Smart Citation